Dal Terzo al Primo Mondo Singapore: un esperimento di successo - Pannozzo, Francesca (Premio Cesare Alfieri «Cum Laude», 2018)
This volume offers an analysis of one of the most interesting contemporary political regimes, the Singapore 'case'. This extremely small island is devoid of natural resources and surrounded by two infinitely larger countries with feelings of hostility towards it. It represents an economic and political experiment which has given birth to a substantially authoritarian, hybrid and yet 'happy' regime, and which has started a rapid development process on whose results its legitimacy is based. Today, Singapore emerges in the world economy as the successful global city to which country leaders around the world look with admiration. However, its extraordinary economic successes have been explicitly accompanied by rather invasive and illiberal policies, thus posing a serious challenge to liberal and democratic Western political systems which, at present, are struggling to provide actual solutions for the same fields of intervention.